Peran Pengembangan Karir dan Komunikasi Organisasi Terhadap Kinerja Karyawan pada PT. Incasi Raya Group - Habibie, M. Rizki; Novianti, Sri; Hariski, M.; Ramdhani, Farhan; Pramusintho, Bagus (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of career development and organizational communication on employee performance at PT Incasi Raya Group. The research method used is descriptive quantitative using primary data obtained through a survey using a questionnaire distributed to employees of PT Incasi Raya Group. Data analysis was carried out using multiple linear regression. The results of the analysis show that career development has a positive and significant influence on employee performance, as does organizational communication. Apart from that, these two variables simultaneously also have a positive and significant effect on employee performance